FRAMING ANALYSIS OF MEDIA ONLINE INDONESIA AGAINTS EXECUTIONS WITHOUT NOTIFICATIONS BY THE GOVERNMENT OF SAUDI ARABIA - Hayatunufus Hayatunufus; Fransiska Maristella; Surwandono Surwandono (Universitas Katolik Soegijapranata, 2024)
This study aims to analyze the views of online media in Indonesia on the case of the execution without notification carried out by Saudi Arabia against Tuti Tursilawati, who is a worker from Indonesia. The researcher uses Murray Edelman's framing analysis theory to analyze media texts to determine how a media conveys news. The research method used is qualitative research with literature review and literature review. Data was collected by accessing three online news portals in Indonesia, including Detik, Kompas, and CNN and obtaining a total of 75 news articles. The news was collected using NCapture and analyzed using NVIVO 12 plus software as a qualitative data analysis tool using features such as crosstab and matrix coding. The research results show that three online media in Indonesia reporting on executions without notification tend to discuss the flawed system and method of communication in Saudi Arabia rather than focusing on Indonesia's failure to save Tuti Tursilawati from execution. Even though the government has sought legal assistance for Tuti Tursilawati, the lack of advocacy and weak political lobbying meant that the execution could not be thwarted. However, this important matter should have been discussed in the media. Based on the results of analysis from 3 online media and 3 points of research using Murray Edelman's overall framing analysis, it tends to corner Saudi Arabia so that it seems that the media is not delivering neutral news but is in favour of the government. This also seems exaggerated because most news highlights the lousy side of Saudi Arabia, so the government's shortcomings in handling it are of little concern.